2019
DOI: 10.2478/aoas-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Rumen Fermentation and Methane Gas Production by Plant Secondary Metabolites (Saponin, Tannin and Essential Oil) – A Review of Ten-Year Studies

Abstract: a wide range of plant secondary metabolites (psM) have been shown to have the potential to modulate the fermentation process in the rumen. the use of plants and plant extracts as natural feed additives has become an interesting topic not only among nutritionists but also other scientists. although a large number of phytochemicals (e.g. saponins, tannins and essential oils) have recently been investigated for their methane (ch 4 ) reduction potential, there have not yet been major breakthroughs that could be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 76 publications
3
37
0
4
Order By: Relevance
“…The present research indicates that the effectiveness of saponins depends on their source, type, and concentration in plant products, thus confirming earlier observations . Moreover, on the basis of our results, we can conclude that saponins extracted from Kometa alfalfa leaves mitigate methane production, total protozoa, bacteria, and methanogen populations less strongly than saponins extracted from Kometa alfalfa roots.…”
Section: Discussionsupporting
confidence: 91%
“…The present research indicates that the effectiveness of saponins depends on their source, type, and concentration in plant products, thus confirming earlier observations . Moreover, on the basis of our results, we can conclude that saponins extracted from Kometa alfalfa leaves mitigate methane production, total protozoa, bacteria, and methanogen populations less strongly than saponins extracted from Kometa alfalfa roots.…”
Section: Discussionsupporting
confidence: 91%
“…During the dry season, most tropical grasses have a high NDF and low CP contents, resulting in limited fermentation of DM, long retention time of digesta and low absorption of volatile fatty acids (VFA) from the rumen, leading to modest daily weight gains in growing cattle and considerable emissions of enteric methane. More than 200 000 plant secondary compounds such as condensed tannins, saponins, flavonoids, organosulfur compounds and essential oils (EOs) have been identified as having potential to mitigate CH 4 emissions in grazing ruminants (Jafari et al, 2019;Molina-Botero et al, 2019a). Secondary compounds in plants should induce a reduction in CH 4 production ( Figure 1) without negatively affecting rumen fermentation or being toxic to the animal, and should ideally improve productive performance, increase economic gains, be easy to handle and be of low cost to farmers.…”
Section: Introductionmentioning
confidence: 99%
“…), among others, have been isolated from fruits and leaves of F. carica that are the main ingredients used in the production of different alcoholic beverages such as wine, liqueur, and spirit. This chapter aims to review the different chemical and biological characteristics found both in raw materials (fruits and leaves) and in the final product (wine, liqueur, and spirit) that have been consumed and known throughout human history.Phytochemicals or plant secondary metabolites are non-nutritive plant metabolites which are essential for plant survival and proper growth and reproduction [23]. Many of these components have bioactivities toward animal biochemistry and metabolism with the ability to provide health benefits.…”
mentioning
confidence: 99%
“…Phytochemicals or plant secondary metabolites are non-nutritive plant metabolites which are essential for plant survival and proper growth and reproduction [23]. Many of these components have bioactivities toward animal biochemistry and metabolism with the ability to provide health benefits.…”
mentioning
confidence: 99%